Islam in Uzbekistan: Organization of the Muslim Board of Uzbekistan - Ugli, Kurbonov (Indonesian Journal Publisher, 2024)
In Uzbekistan, religion is an integral part of the country's cultural and spiritual traditions and the basis of the spiritual maturity of the population. Today in Uzbekistan there are about 2300 religious organizations belonging to representatives of more than 130 nationalities and peoples and members of 16 religious denominations. People of different nationalities and religions live peacefully on the basis of the principle of tolerance. The government has been closely supporting the activities of each denomination. Muslim Board of Uzbekistan is one of the most influential non-governmental non-profit organizations in Uzbekistan. Ensuring the unity of believers and Muslims, clearly and correctly conveying Islamic rules to the people, creating facilities for obedience and worship, maintaining the ideological unity of Muslims, researching the historical heritage of our ancestors, carrying out charity work, and ensuring harmony in society. These are the main areas of activity of the Muslim Board of Uzbekistan.